PENGARUH INTELLECTUAL CAPITAL, KEPUTUSAN INVESTASI DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN MULTINASIONAL SEKTOR NON-CYCLICALS YANG TERDAFTAR DI BEI (PERIODE 2019-2023) - Sena, Teresia; Zenabia, Tsarina (Jurnal Nusa Akuntansi, 2025)
This study aims to analyze the effect of intellectual capital, investment decisions and financial performance on firm value in manufacturing companies in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange in 2019-2023. Firm value is measured by Price Book Value (PBV), intellectual capital is measured by Value Added Intellektual Capital (VAIC), investment decisions are measured by Price Earning Ratio (PER) and financial performance is measured by Return On Asset (ROA). The sample selection technique in this study used purposive sampling and obtained 32 sample companies. Panel data regression hypothesis testing using eviews software version 9. The results of this study indicate that Intellectual capital, investment decisions and financial performance simultaneously have a significant positive effect on firm value. Intellectual capital has a positive and significant effect on firm value. Investment decisions have a positive and significant effect on firm value. Financial performance has no positive and significant effect on firm value.